2018
DOI: 10.1186/s12887-018-1120-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in paediatric arterial hypertension: a cross-sectional study

Abstract: BackgroundThe prevalence of paediatric hypertension is increasing worldwide, especially due to the childhood obesity epidemic, and is an important public-health concern. While the Health-Related Quality of Life (HRQoL) was already shown to be impaired in the adult hypertensive population, a scarcity of data still exists on HRQoL in paediatric hypertensive patients. Our purpose was thus to assess the HRQoL of children and adolescents with arterial hypertension, using self- and proxy-reports, and to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
3
1
2
Order By: Relevance
“…Our results from the questioning of children with normal BP in general terms are consistent with data from other studies. The Total Score HRQoL for healthy schoolchildren, according to different authors, ranges from 72.7 to 86.9 points [21][22][23][24]. In our study, the Total Score HRQoL in the control group was 79.05 [12.25].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our results from the questioning of children with normal BP in general terms are consistent with data from other studies. The Total Score HRQoL for healthy schoolchildren, according to different authors, ranges from 72.7 to 86.9 points [21][22][23][24]. In our study, the Total Score HRQoL in the control group was 79.05 [12.25].…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, data reported by Petek et al [24] showed that high BP was associated with good HRQoL parameters in children and adolescents [25], including those with high BP due to chronic kidney disease [26].…”
Section: Resultsmentioning
confidence: 82%
“…It is important to remember that the changes in the functional state of the BP regulation systems observed in our study, not only depend on psycho-emotional stress, but can also produce a negative impact on the health of schoolchildren in general, thus closing a "vicious circle". It is known that hypertension is perceived at the subjective level as feeling bad and negative mood that reduces the quality of social life of adolescents [34]. Objective studies have shown that adolescents with high BP demonstrated lower effectiveness in cognitive tests [35].…”
Section: Discussionmentioning
confidence: 99%
“…Сучасні наукові бази даних мають обмежену кількість робіт, присвячених вивченню HRQoL у дітей з АГ і високим нормальним АТ. У більшості з них не використовували дані АМАТ, а діагностику АГ проводили за офісним вимірюванням АТ, що, на наш погляд, не дозволяє чітко розмежувати дітей з високим нормальним АТ і початковими етапами розвитку АГ.Зокрема, у дослідженні, проведеному в Словенії[20], не враховували ступінь підвищення АТ. У статті вказується, що при лікуванні більшості пацієнтів використовувалась лише модифікація способу життя, це дозволяє припустити, що ступінь підвищення АТ був незначним.…”
unclassified
“…Як і в дослідженнях, проведених у Словенії, у нашій роботі найменша кількість балів у дітей з АГ була отримана за шкалою емоційного функціонування. Підвищений рівень АТ не вплинув на рівень соціального функціонування як у нашій, так і в указаній роботі.На відміну від даних, що повідомляли Petek et al[20], в інших дослідженнях було встановлено, що високий показник АТ пов'язаний з добрим HRQoL у дітей[21].У дослідженні A. Berendes et al [21] брали участь 7697 пацієнтів віком від 11 до 17 років. Основним висновком цього дослідження було те, що підлітки з підвищеним АТ виявили значно кращі показники якості життя і нижчий рівень дистресу.…”
unclassified